2020
DOI: 10.1111/ctr.13985
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transplant survival in adult congenital heart disease patients as compared to dilated and ischemic cardiomyopathy patients; an analysis of the thoracic ISHLT registry

Abstract: Congenital heart defects (CHD) are the most common type of birth defects and account for approximately one-third of all major congenital anomalies. 1 Worldwide, the prevalence has been increasing over time, and CHD now affects 1.35 million newborns every year. 1 With advances in cardiology and cardiac surgery, 90% of these patients survive into adulthood where they are then at risk of various late complications including arrhythmia, heart failure, pulmonary hypertension, and sudden cardiac death. 2,3 Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…represented a European cohort where only 1/3rd of evaluated patients were transplanted. One year outcomes were significantly better as compared to outcomes from the thoracic ISHLT registry which reported a 78.3% survival and comparable to outcomes in patients with ischemic (84.3%) and dilated cardiomyopathy (86.2%) 11 . Kaplan–Meier survival analysis demonstrated that our post‐transplantation group had improved 10‐year mortality (69.6%) compared to 59.3% reported by other groups 12 .…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…represented a European cohort where only 1/3rd of evaluated patients were transplanted. One year outcomes were significantly better as compared to outcomes from the thoracic ISHLT registry which reported a 78.3% survival and comparable to outcomes in patients with ischemic (84.3%) and dilated cardiomyopathy (86.2%) 11 . Kaplan–Meier survival analysis demonstrated that our post‐transplantation group had improved 10‐year mortality (69.6%) compared to 59.3% reported by other groups 12 .…”
Section: Discussionsupporting
confidence: 46%
“…One year outcomes were significantly better as compared to outcomes from the thoracic ISHLT registry which reported a 78.3% survival and comparable to outcomes in patients with ischemic (84.3%) and dilated cardiomyopathy (86.2%). 11 Kaplan-Meier survival analysis demonstrated that our post-transplantation group had improved 10year mortality (69.6%) compared to 59.3% reported by other groups. 12 Interestingly, our results showed worse survival (42.1%) in the waitlisted population who awaited transplantation, compared to other studies looking at a similar population which reported a 1-year survival of 89%, 63% at 24 months, and 63% at 48 months.…”
Section: Triaging Listing Status Correlates With Survival Outcomesmentioning
confidence: 46%
“…In the updated International Society for Heart and Lung Transplantation (ISHLT) database (as of 2020), there were a total of 30,130 patients with HT between 2004 and 2014. Of these, 1839 were related to CHD (one-year survival 78.3%), 16,444 to dilated cardiomyopathy (one-year survival 86.2%) and 12,247 to ischemic heart disease (survival of 84.3%) [102]. In this regard, patients with FP demonstrated 1.7-times higher risk of death from complications in the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 98%
“…According to a position statement from the European Society of Cardiology, cardiomyopathy is a myocardial disorder in which the heart muscle is structurally and functionally abnormal, in the absence of coronary artery disease, hypertension, valvular disease and congenital heart disease sufficient to cause the observed myocardial abnormality [ 135 ]. In this review we will focus on the following cardiomyopathies: diabetic cardiomyopathy [ 136 ], hypertrophic cardiomyopathy, dilated cardiomyopathy [ 137 ], secondary hypertrophic cardiomyopathy [ 74 ], post-transplant cardiomyopathy [ 138 ], iron overload cardiomyopathy [ 139 ], septic cardiomyopathy [ 140 ], doxorubicin-induced cardiomyopathy [ 141 ], and radiation-induced cardiomyopathy [ 142 ] in light of their high clinical relevance and the available data so far published. All of these cardiomyopathies are associated, by definition, with cardiomyocyte death.…”
Section: Ferroptosis and Cvdsmentioning
confidence: 99%
“…Data show that NK cells play a role in CAV formation via a CD8 + T-cell mediated mechanism [ 194 ] and CD8 + T-cells are known to release interferon-gamma which can reduce the synthesis of SLC7A11 and hence favor ferroptosis [ 195 ]. Post-transplant cardiomyopathy is a very complex condition with multiple mechanisms involved [ 138 ]. Although the role of ferroptosis in post-transplant cardiomyopathy has been established mainly in favoring early inflammation and late immune response, many more aspects should be investigated to have an unambiguous setting.…”
Section: Ferroptosis and Cvdsmentioning
confidence: 99%